The design of Janus black phosphorus quantum dots@metal–organic nanoparticles for simultaneously enhancing environmental stability and photodynamic therapy efficiency. (26th February 2019) - Zhang, Da; Lin, Ziguo; Lan, Shanyou; Sun, Haiyan; Zeng, Yongyi; Liu, Xiaolong
Abstract : We have fabricated Janus nanoparticles based on black phosphorus quantum dots and metal–organic particles for PDT enhancement. Abstract : Although newly-developed black phosphorus quantum dots (BPQDs) with unique photocatalytic properties have attracted much attention for biomedical applications, especially phototherapy, the environmental instability and weak photocatalytic activity of BPQDs remains a considerable challenge preventing their clinical application. Herein, we have designed new Janus nanoparticles (J-MOPs) based on BPQDs and tetrahydroxyanthraquinone (THQ)–Cu metal–organic particles (MOPs) to simultaneously improve the environmental stability and photocatalytic activity for the PDT treatment of cancers. The J-MOPs were simply assembled from BPQDs and THQ via Cu-mediated P–Cu–THQ "host–metal–guest" coordination effects. The encapsulation of BPQDs inside J-MOPs and P–Cu bonds effectively isolated BPQDs from water–air and occupied the P lone-pair electrons, respectively, to improve the stability of BPQDs. Furthermore, the dramatic electron–hole separation and migration abilities of J-MOPs increased the reactivity toward O2, which enhanced singlet oxygen ( 1 O2 ) generation against cancers compared with BPQDs alone when exposed to 670 nm laser irradiation. Intriguingly, tumor acid-triggered J-MOPs degradation resulted in the release of Cu 2+ ions that further served as a Fenton-like agent to generate ˙OH from H2 O2, which enhanced the antitumor effects of the J-MOPs. Therefore, we have highlighted the potential of J-MOPs as a photocatalyst for photodynamic cancer therapy.